Genetics in pulmonary arterial hypertension in a large homogeneous Japanese population. Issue 1 (25th January 2018) - Gamou, S.; Kataoka, M.; Aimi, Y.; Chiba, T.; Momose, Y.; Isobe, S.; Hirayama, T.; Yoshino, H.; Fukuda, K.; Satoh, T.
Abstract : Pulmonary arterial hypertension (PAH) is a rare but serious disease with a grave prognosis. Bone morphogenetic protein type 2 receptor ( BMPR2 ) gene is a strong pathogenic factor for PAH. As a collaborative team from Kyorin University and Keio University in Japan, we have analyzed the BMPR2 gene in 356 probands and more than 50 family members, including secondary patients. Importantly, the study population is a racially, ethnically, and socially homogeneous population. In PAH patients, there is a high incidence of unique mutations in BMPR2, and several mutations are frequently observed in the Japanese population, suggesting that these common and recurring mutations may be highly pathogenic or have high penetrance, explaining why they are found frequently throughout the world. We have also mapped each breakpoint of exonic deletions/duplications and found that most break and rejoining points are in the Alu elements. Reviewing the distribution of the reported mutations on each exon of BMPR2 revealed that the number and frequency of mutations are imbalanced among exons. The penetrance of BMPR2 gene mutations was 3‐fold higher in females than males. Full elucidation of BMPR2 ‐mediated pathogenic mechanisms in PAH requires persistent efforts to achieve precision or individualized medicine as a therapeutic strategy for PAH. Abstract :